Stigma and Therapy Completion for Latent Tuberculosis among Haitian-origin Patients - Jeannine Coreil; Michael Lauzardo; Heather Clayton (University of North Florida, 2010)
A prospective cohort study of LTBI treatment conducted within the Haitian population of South Florida investigated the predictive association between illness-related stigma among patients near the beginning of treatment and completion of preventive therapy. Factors associated with perceived stigma were also investigated. Ninety patients from Broward and Palm Beach counties were administered a questionnaire that included items related to illness history, perceptions and understanding of latent tuberculosis, and a 25-item stigma scale adapted from previously developed measures of tuberculosis-related stigma. Therapy completion was determined through a follow-up chart review. Data analyses compared patients who completed therapy with those who defaulted on a number of variables including perceived stigma. No association was found between perceived stigma or demographic characteristics and adherence to preventive therapy. Perceived stigma was associated with patient report of illness-related distress and was higher among patients who were lost to follow up. Some evidence suggested that stigma was higher among contacts of cases, patients with limited understanding of the condition, and patients who were more closely monitored during treatment. Case management should focus on patient-centered approaches to education and counseling about LTBI that address patient understanding of the condition and concerns about its physical and psychosocial effects.